High-entropy alloy: challenges and prospects. Issue 6 (July 2016) - Ye, Y.F.; Wang, Q.; Lu, J.; Liu, C.T.; Yang, Y.
Abstract : High-entropy alloys (HEAs) are presently of great research interest in materials science and engineering. Unlike conventional alloys, which contain one and rarely two base elements, HEAs comprise multiple principal elements, with the possible number of HEA compositions extending considerably more than conventional alloys. With the advent of HEAs, fundamental issues that challenge the proposed theories, models, and methods for conventional alloys also emerge. Here, we provide a critical review of the recent studies aiming to address the fundamental issues related to phase formation in HEAs. In addition, novel properties of HEAs are also discussed, such as their excellent specific strength, superior mechanical performance at high temperatures, exceptional ductility and fracture toughness at cryogenic temperatures, superparamagnetism, and superconductivity. Due to their considerable structural and functional potential as well as richness of design, HEAs are promising candidates for new applications, which warrants further studies.